Pemanfaatan Tumbuhan pada Ritual Tradisi Mandi Pengantin Masyarakat Suku Dayak Bakumpai di Kalimantan Selatan - Yusuf, Novita Anggriani; Dharmono, Dharmono; Badruzsaufari, Badruzsaufari; Mahdian, Mahdian (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2023)
The tradition of bridal bathing or called mandi bapapai is carried out from generation to generation by the Dayak Bakumpai tribe in Lepasan Village, Barito Kuala Regency, South Kalimantan. This tradition is a traditional event that utilizes plants as a symbol in its implementation. The purpose of this article is to determine the local potential of plants used in traditional events and focuses on the use of plant species and parts used. This research uses a descriptive approach to produce a systematic, factual, and accurate description of the facts, characteristics, and relationships between plant phenomena used in the traditional ritual of bridal bathing or bathing bapapai. The results of research through interview instruments show that the community utilizes as many as nine species in seven families in the traditional ritual of bridal bathing, including Rosaceae (Rosa hybrida L.), Oleaceae (Jasmimum sambac), Anonaceae (Cananga odorata), and Magnoliaceae (Michelia champaca L). Araceae (Areca catechu Cocos nucifera), Poaceae (Saccharum officinarum Oriza sativa), and Musaceae (Musa paradisiaca L.).